Patient education and anesthesia choice for total knee arthroplasty. Issue 9 (September 2017) - Elkassabany, Nabil M.; Abraham, Daniel; Huang, Stephanie; Kase, Brandon; Pio, Finnah; Hume, Eric; Israelite, Craig; Liu, Jiabin
Highlights: Spinal anesthesia (S A) may be associated with improved outcomes in TKA. Rate ofS A in the US is only around 25%. Lack of information aboutS A may be a barrier to its increased use. "Joints class" is a preoperative educational session offering anesthesia information. Attendance of the joints class was associated with increase in the rate ofS A. Abstract: Objectives: Spinal anesthesia (S A) for Total KneeArthroplasty (TKA) may be associated with better patients' outcomes. This study aims to assess the association between preoperative education about the advantage ofS A over general anesthesia (GA) for TKA and the likelihood of patient choice of NA. Methods: Patients undergoing unilateral primary TKA were identified. Type of anesthesia (GA orS A), attendance of the (joints class), patient demographics, ASA status, anticoagulation status, and diagnosis of back problems were recoded. Regression analysis was used to assess the association between the type of anesthesia and attendance of the joints class. Results: 1010 patients were identified to have unilateral primary TKA. 31% of patients attended the joint class. Patients who attended the joints class were more likely to receiveS A when compared to those who did not attend (OR = 1.7, CI: 1.2–2.5, P = 0.004) after adjusting for other variables. Conclusion: Preoperative education about advantages ofS A may be associated with an increase in patients receivingS A for TKA. Practice implications: Increase in patients receivingS A for TKA may improve outcomes.